2018
DOI: 10.1111/cts.12582
|View full text |Cite
|
Sign up to set email alerts
|

Design and Conduct Considerations for First‐in‐Human Trials

Abstract: A milestone step in translational science to transform basic scientific discoveries into therapeutic applications is the advancement of a drug candidate from preclinical studies to initial human testing. First-in-human (FIH) trials serve as the link to advance new promising drug candidates and are conducted primarily to determine the safe dose range for further clinical development. Cross-functional collaboration is essential to ensure efficient and successful FIH trials. The aim of this publication is to serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 46 publications
0
87
0
Order By: Relevance
“…Safety pharmacology/pharmacokinetic studies evaluate the impact of an investigational product on the respiratory, cardiovascular, and central nervous systems. The concern that a new therapy could result in an arrhythmia that was not detected in preclinical animal models is the underlying reason that initial cardiovascular assessments in early human studies often include an evaluation of a drug's potential for prolongation of the QT interval 12 …”
Section: Preclinical Drug Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Safety pharmacology/pharmacokinetic studies evaluate the impact of an investigational product on the respiratory, cardiovascular, and central nervous systems. The concern that a new therapy could result in an arrhythmia that was not detected in preclinical animal models is the underlying reason that initial cardiovascular assessments in early human studies often include an evaluation of a drug's potential for prolongation of the QT interval 12 …”
Section: Preclinical Drug Developmentmentioning
confidence: 99%
“…The dose range in animal studies should be broad enough that the no observed adverse effect level (NOAEL) is established, which should be greater than the maximum exposure expected to be used in humans. The NOAEL is the most common method for determining a safe starting dose for human trials, but it is not the only method 12 …”
Section: Preclinical Drug Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size of 10 participants per cohort is a commonly used number in early studies. 13 The steps recommended in the US Food and Drug Administration's Guidance for Industry: Estimating the Maximum Safe Starting Dose in Initial Clinical Trials for Therapeutics in Adult Healthy Volunteers 14 were followed for the estimation of the starting dose. On normalizing the experimentally determined nontoxic dosage level for surface area, the most sensitive preclinical animal species examined was the dog.…”
Section: Single Ascending Dose Study Proceduresmentioning
confidence: 99%